KNN based high dielectric constant X9R ceramics with fine grain structure and energy storage ability. Issue 11 (9th July 2021) - Hui, Kezhen; Chen, Lingling; Cen, Zenyong; Zhao, Peiyao; Yu, Yan; Guo, Limin; Wang, Xiaohui; Li, Longtu
Abstract: In this study, SrZrO3 doped K0.5 Na0.5 NbO3 ceramics with Cu, Sn, and Mn as sintering aid are prepared to modulate the temperature stability by conventional solid‐state sintering, and samples are denoted as KNNC‐100 x SZ, KNNS‐100 x SZ, and KNNM‐100 x SZ, respectively, where x is the doping amount. The average grain size of the KNNC‐12.75SZ sample was ~150 nm. The dielectric constant of KNNC‐13.00SZ was 2072 and its dielectric loss was 1.8% at room temperature, with a wide temperature stability range from −55°C to 220°C satisfying the X9R criteria. The discharge energy density of KNNC‐12.75SZ reached 1.47 J/cm 3 at room temperature; therefore, the modified KNN is a promising candidate for X9R dielectrics with a fine grain structure and potential anti‐reduction capability due to the absence of variable valence elements. The modified KNN can also be applied to energy storage capacitors subjected to high working temperatures.